SCIENCE, TECHNOLOGY, AND SOCIETY (STS)-BASED TEACHER PEDAGOGICAL STRATEGIES FOR CULTIVATING GROWTH MINDSET IN EARLY CHILDHOOD EDUCATION - A. Rezky Nurhidaya S; Sadaruddin (Academic Bright Collaboration, 2026)
This study aimed to: (1) analyse the initial conditions of children's growth mindset and grit deficiencies, (2) describe the implementation of Science, Technology, and Society (STS)-based pedagogical strategies integrated through traditional games (asing-asing, bom, and kucing dan tikus), and (3) analyse their empirical impact on the development of early childhood growth mindsets. This research used an explanatory sequential mixed-methods design. Quantitative data from a quasi-experimental setup (N=30) were analyzed using the Wilcoxon signed-rank test. These outputs were then sequentially integrated and triangulated with qualitative data obtained from semi-structured teacher interviews, field observations, and audio-visual documentation logs involving children and teachers at Raudhatul Athfal (RA) Ihya Ulum in Makassar City. The results indicated that children's initial conditions were dominated by a rigid fixed mindset and social-emotional deficiencies, characterised by persistent egocentrism, low perseverance, and a tendency to avoid difficult tasks. The implementation of STS-based pedagogical strategies through culturally rooted traditional games, combined with adaptive teacher scaffolding and effort-based reinforcement, has been proven to create meaningful learning experiences. Post-intervention empirical analysis demonstrated a profound statistical leap in the experimental group, with growth mindset mean scores rising significantly from 16.30 to 20.70 (p=0.005), in sharp contrast to the control group’s stagnation. Qualitative triangulation confirmed that this active approach successfully dismantled egocentric isolation, nurtured emotional self-regulation, and enabled children to constructively reframe failures into strategic opportunities for growth. This study bridges the gap between cognitive STS frameworks and affective mindset theories. Practically, it provides a cost-effective, easily applicable, and culturally responsive curriculum model for preschool educators to strengthen early childhood integrative experience-based learning, particularly within the context of Islamic education. Previous STS research heavily emphasises cognitive outputs, leaving critical affective dimensions like grit and mindset transformation unexplored within preschool Islamic frameworks. Another research gap lies in the lack of case-centered classroom studies illustrating the real-time implementation of these pedagogical strategies. Therefore, this study fills these gaps by examining how an STS-infused traditional games strategy structurally transforms fixed mindsets into growth mindsets in an RA setting. This study provides a practical, low-cost blueprint for teachers to foster psychological resilience and 21st-century social competence through structured play.